The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1540-6040.2009.01268.x
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Attachment in the Multiethnic Metropolis

Abstract: In acknowledging that patterns of neighborhood attachment—a key component in the maintenance of neighborhood vitality—may shift as a result of growing racial and ethnic diversity, this study develops a multiethnic and multilevel framework to examine the link between racial diversity and attachment among Los Angeles residents. The expansion of the Asian and Hispanic populations may affect attachment patterns if group members exhibit different levels of attachment compared with blacks and whites, due to factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
2
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(102 citation statements)
references
References 57 publications
4
93
2
3
Order By: Relevance
“…First, these findings support our fourth hypothesis-(H4) community connection is increased by organizational membership-reflecting a robust body of research (Greif 2009;Putnam 2000Putnam , 2007Sampson 2012). Building on the existing work, we found that even when accounting for segregation and socioeconomic status of neighborhoods, participation in an organization improves one's community connection.…”
Section: Discussionsupporting
confidence: 76%
“…First, these findings support our fourth hypothesis-(H4) community connection is increased by organizational membership-reflecting a robust body of research (Greif 2009;Putnam 2000Putnam , 2007Sampson 2012). Building on the existing work, we found that even when accounting for segregation and socioeconomic status of neighborhoods, participation in an organization improves one's community connection.…”
Section: Discussionsupporting
confidence: 76%
“…Comparative data suggest that the notion of neighborhood identity (or the related concept, ''neighborhood attachment") is a common, perhaps universal, attribute of neighborhoods cross-culturally. Neighborhood identity is reported in ethnographic studies of nonwestern cities (Mills, 2004), in documentary analyses of preindustrial cities (Marcus, 1989;Smail, 2000), and in sociological research on modern industrial cities (Greif, 2009). The topic of identification with one's district may be more variable.…”
Section: Bottom-up Processesmentioning
confidence: 98%
“…Se ha usado el tipo de vivienda, el tipo de colonia, la condición migratoria, así como otras variables regionales, demográficas y socioeconómicas. En particular se ha estudiado cómo difiere la satisfacción con la colonia de: los residentes locales y los extranjeros (Li, 2012;Oktay et al, 2012); los residentes beneficiarios de programas de vivienda gubernamentales en áreas urbanas frente a los de los sitios suburbanos (Cook, 1988); los residentes en áreas centrales en comparación con los que viven en la periferia de las áreas centrales (Loo, 1986); los residentes en suburbios convencionales respecto a los que viven en colonias que tienen diseños tradicionales (Lavejoy et al, 2010); las personas que residen en colonias con dife-rentes esquemas o tipos de vivienda (Djebami y Al-Abed, 2000;Gruber y Shelton, 1987); los residentes de acuerdo con su raza (Greif, 2009;Lee et al, 1991;Hunter, 1974;Campbell et al, 1976;Fried, 1982;Ahlbrandt, 1984); las comunidades compactas frente a las mixtas, que concentran los lugares de empleo y vivienda, así como el uso eficiente del suelo y la reducción de las distancias (Yang, 2008); las comunidades que cobran cuotas de mantenimiento en contraposición con aquellas que no tienen esa práctica (Chapman y Lombard, 2006). Asimismo se ha analizado la influencia de las características sociodemográficas y el tipo de colonia (clasificadas en áreas afluentes y desfavorecidas) en el grado de satisfacción con la colonia (Hipp, 2009;Parkes et al, 2002), así como la influencia de la mezcla de residentes, en términos del régimen de propiedad en la colonia (Kearns y Mason, 2007).…”
Section: Literatura En Torno a La Satisfacción Con La Coloniaunclassified